A Virtual Library for the Maghreb? Opportunities and Challenges of Open Access to Scientific Information. - Hanae LRHOUL; Abderrahim AMEUR (Journal of Information Sciences, 2022)
Our study aims to analyze the landscape of scientific communication in the North Africa, in light of the new paradigms of scientific communication and knowledge sharing. We wish to identify the main initiatives carried out in the Northern African countries (open archives and open access journals). We wish first to reflect on the opportunities and challenges of developing open access, in the other hand, we analyze we try to propose the best path of open access that corresponds to the context of the region. We also aim to propose a national digital library model for the promotion of the Maghreb scientific heritage and increase the impact of Maghreb researchers. To attend our objective, we are using the documentary approach and consulting several international sources and directories to analyze the evolution of open access in the region.